Success Throughout Gacha Game Satisfaction by using D&M Model from Students in Batam - Junaidi Kwok; Tony Wibowo (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
Gacha games, a prominent subgenre in the realm of online and mobile gaming, have gained widespread popularity for their distinctive monetization approach involving random in-game purchases and the acquisition of virtual items or characters through virtual loot boxes. Despite the ongoing debates and controversies surrounding ethical implications and parallels to gambling, Gacha games have demonstrated significant success and consistently engaged a diverse player base. This research aims to unravel the mysteries of this success and assess its correlation with user satisfaction. The study adopts the DeLone and McLean Information Systems Success Model, tailored for qualitative data analysis. Titled "Success Throughout Gacha Game Satisfaction by using D&M Model from Students in Batam," this research delves into the perceptions and experiences of students in Batam, Indonesia, regarding various Gacha games, including AzurLane, Fate/GO, Honkai Impact, Arknights, Blue Archive, Genshin Impact, Honkai: Star Rail, and other notable titles.